2002
DOI: 10.1080/0899022021000037755
|View full text |Cite
|
Sign up to set email alerts
|

The influence of increased muscle spindle sensitivity on Achilles tendon jerk and H-reflex in relaxed human subjects

Abstract: Whether the fusimotor system contributes to reflex gain changes during reinforcement maneuvers is re-examined in the light of new data. Recently, from direct recordings of spindle afferent activity originating from ankle flexor muscles, we showed that mental computation increased the muscle spindle mechanical sensitivity in completely relaxed human subjects without concomitant alpha-motoneuron activation, providing evidence for selective fusimotor drive activation. In the present study, the effects of mental c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0

Year Published

2004
2004
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 51 publications
3
41
0
Order By: Relevance
“…An increased firing rate from primary muscle spindle afferents and increased stretch sensitivity during mental computation have also been demonstrated (26). In a study of a mental computation task, Rossi-Durand and colleagues (28) observed that the increases in stretch reflex amplitude occurred without H-reflex changes, indicating changes in muscle spindle sensitivity rather than changes in ␣-motoneuron excitability or presynaptic inhibition on Ia afferents. They ascribed the increased stretch sensitivity during mental computation to a fusimotor sensitization of muscle spindles and suggested that, in relaxed subjects performing mental computation, the presetting of the fusimotor activation in priming spindle sensitivity could prepare the muscle spindles to better play their role in proprioception and motor control.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…An increased firing rate from primary muscle spindle afferents and increased stretch sensitivity during mental computation have also been demonstrated (26). In a study of a mental computation task, Rossi-Durand and colleagues (28) observed that the increases in stretch reflex amplitude occurred without H-reflex changes, indicating changes in muscle spindle sensitivity rather than changes in ␣-motoneuron excitability or presynaptic inhibition on Ia afferents. They ascribed the increased stretch sensitivity during mental computation to a fusimotor sensitization of muscle spindles and suggested that, in relaxed subjects performing mental computation, the presetting of the fusimotor activation in priming spindle sensitivity could prepare the muscle spindles to better play their role in proprioception and motor control.…”
Section: Discussionmentioning
confidence: 97%
“…A mental computation task (28) and unpleasant picture viewing (3) both clearly facilitated the stretch reflex in the soleus muscle. An increased firing rate from primary muscle spindle afferents and increased stretch sensitivity during mental computation have also been demonstrated (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A cognitive task has been shown to affect the H reflex in humans (38). It is therefore possible that neural activity via a cognitive task may modulate other neural signals at the level of the spinal cord in a manner similar to the way in which central motor command that has been shown to interact with afferent feedback (14).…”
Section: Discussionmentioning
confidence: 99%
“…The H reflex reflects spinal excitability through the integration of afferent pathways and reflex activation of ␣ motoneurons. 29 Furthermore, a recent human study 33 showed that the changes in activity of muscle spindle primary endings are generally positively correlated with those of both the mechanically (tendon jerk) and electrically (Hoffman) elicited reflexes. However, the TVR does not correspond solely to a monosynaptic reflex between spindle afferents and spinal motor neurons.…”
Section: Figurementioning
confidence: 98%